18. POTENSI EKSTRAK AIR DAUN SERNAI (Wedelia biflora) SEBAGAI ANTINYERI PADA MENCIT (Mus musculus) The Potency of Wedelia biflora Leaf Water Extract as Pain killer on Mice (Mus musculus) - Abdul Hayi Amarta Ali (Universitas Syiah Kuala, 2016)
The purpose of this research was to find out the potency of Wedelia biflora water extract as pain killer. Completely randomized design (CDR) was used in this study. A total of 30 mice (Mus musculus) were divided into five treatment groups. Mice in group 1 (P0) were administered with mefenamat (positive control) and mice group 2 (P1) were only given aquadest (negative control). Mice in another3 groups (P2, P3, and P4) were administered with Wedelia biflora water extract with the concentration of 100, 75, and 50%, respectively. The painful response time was done using hot plate method and observed at 0, 30, 60, and 90 minutes, whereas abdominal writhing method was applied to count the total of writhing. Data were analyzed using ANOVA followed by Duncan. Result showed that Wedelia biflora water extract with various levels of concentration were affect significantly (P0.05) compared to negative control but no significant different (P0.05) with positive control. The analgesic potency showed significant effect (P0.05) at concentration of 100 and 75% compared to negative control, but no significant different (P0.05) compare to positive control on both hot plate methods and abdominal writhing method, whereas 50% concentration showed analgesic potency (P0.05) only on hot plate method. In conclusion, Wedelia biflora water extract is potential as analgesic on mouse and shows no significant different with mefenamat. ____________________________________________________________________________________________________________________ Key words: analgesik, Wedelia biflora, painful, total of writhe